Influence of Health Promotion on Infant and Young Child Feeding (IYCF) Behavior by Mothers of Toddlers - Rotua Sumihar Sitorus (JURNAL KEBIDANAN KESTRA (JKK), 2025)
Background: Malnutrition in infants and young children, especially stunting, remains a major public health challenge in Indonesia. Health promotion is believed to improve appropriate Infant and Young Child Feeding (IYCF) practices. Objective: To analyze the influence of health promotion on IYCF behavior among mothers of toddlers in the working area of Lubuk Pakam Health Center. Research Methods: This was a quantitative analytic study with a cross-sectional design. A total of 120 mothers with children aged 6–24 months were selected using purposive sampling. Data were collected through structured questionnaires and analyzed using Chi-square tests. Results: About 70% of respondents had received health promotion, mainly through Posyandu (60.7%). Most mothers (62.5%) demonstrated good IYCF practices. A significant relationship was found between health promotion and IYCF behavior (p=0.0001). Conclusion: Health promotion significantly influences improved IYCF practices. Strengthening community-based health promotion, improving maternal nutrition literacy, and optimizing primary health care services are crucial for enhancing IYCF practices and reducing stunting rates.